Blackberry Regrowth and Persistence Responses to Defoliation in Mixed Rhizoma Peanut‐Grass Swards. Issue 3 (1st May 2016) - Krueger, N.C.; Sollenberger, L.E.; Vendramini, J.M.B.; Na, C.; Mullenix, M.K.; Aguiar, A.D.; Blount, A.R.
Abstract : Sand blackberry ( Rubus cuneifolius Pursh) is a troublesome perennial weed in Florida rhizoma peanut ( Arachis glabrata Benth.)–grass pastures. The degree to which it can be controlled by defoliation is not well understood. In 2011 and 2012, blackberry regrowth and persistence responses were assessed by clipping every 35 d to three stubble heights (8, 16, and 24 cm), with or without simultaneous removal of all leaf from remaining stubble. Blackberry dry matter harvested decreased linearly (12.8 to 8.5 g m −2 ) as clipping stubble height increased when remaining stubble leaf was removed, but there was a linear increase in blackberry harvested with increasing clipping stubble height (12.1 to 26.0 g m −2 ) if remaining stubble leaf was not removed. Across stubble heights, cumulative change in blackberry cover across the 2 yr was −15% units if stubble leaf was removed compared with +1% unit when leaf remained intact. As stubble height increased from 8 to 24 cm, blackberry cover increased linearly, both when stubble leaf was removed (−18 to 0% units, respectively) and when leaf remained intact (−12 to +17% units, respectively). In Year 1, blackberry stem density decreased 10 stems m −2 when stubble leaf was removed and 4 stems m −2 when leaf remained intact, but there was no effect of leaf removal in Year 2. Both clipping stubble height and removal of leaf mass affected blackberry regrowth and cover responses, suggesting that combining leaf removal by browsing animals with periodic close mowing will reduce blackberry cover, mass, and stem density.